Guidelines on the management of common bile duct stones (CBDS). Issue 7 (5th March 2008) - Williams, E J; Green, J; Beckingham, I; Parks, R; Martin, D; Lombard, M
Abstract : The last 30 years have seen major developments in the management of gallstone-related disease, which in the United States alone costs over 6 billion dollars per annum to treat. Endoscopic retrograde cholangiopancreatography (ERCP) has become a widely available and routine procedure, whilst open cholecystectomy has largely been replaced by a laparoscopic approach, which may or may not include laparoscopic exploration of the common bile duct (LCBDE). In addition, new imaging techniques such as magnetic resonance cholangiography (MR) and endoscopic ultrasound (EUS) offer the opportunity to accurately visualise the biliary system without instrumentation of the ducts. As a consequence clinicians are now faced with a number of potentially valid options for managing patients with suspected CBDS. It is with this in mind that the following guidelines have been written.